The Concept of Intertextuality and the Importance of Dialogism and the Utterance - Aziza Mirzaeva Shavkatovna (Researchparks Publishing, 2022)
This article explores the concept of Intertextuality primarily from a theoretical point of view and analyzes the concept of Intertextuality and its further development. The article focuses on in the exploration of the theoretical approaches are: the text, or the object of literary study, the author, and the reader, and the manner in which meaning is produced through the interaction/agency of these three elements.